Margins of international banking: is there a productivity pecking order in banking, too? - Claudia M. Buch; Cathérine Tahmee Koch; Michael Koetter (Deutsche Bundesbank, 2009)
Modern trade theory emphasizes firm-level productivity differentials to explain the cross-border activities of non-financial firms. This study tests whether a productivity pecking order also determines international banking activities. Using a novel dataset that contains all German banks' international activities, we estimate the ordered probability of a presence abroad (extensive margin) and the volume of international assets (intensive margin). Methodologically, we enrich the conventional Heckman selection model to account for the self-selection of banks into different modes of foreign activities using an ordered probit. Four main findings emerge. First, similar to results for non-financial firms, a productivity pecking order drives bank internationalization. Second, only a few non-financial firms engage in international trade, but many banks hold nternational assets, and only a few large banks engage in foreign direct investment. Third, in addition to productivity, risk factors matter for international banking. Fourth, gravity-type variables have an important impact on international banking activities.
Keywords: F3; G21; 330; International banking; extensive and intensive margin; productivity pecking order; ordered probit; selection models; Internationale Bank; Bankgeschäft; Internationale Markteintrittsstrategie; Produktivität; Probit-Modell; Schätzung; Deutschland